PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSETS TURNOVER, DAN SALES GROWTH TERHADAP RETURN ON ASSET PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019 - ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 1 No 1 (2021): Vol. 1 No. 1 (2021): LUCRUM, 2022)
This study aims to analyze the effect of Current Ratio, Debt to Equity Ratio, Total Assets Turnover and Sales Growth on Return on Assets in food and beverage sub-sector manufacturing companies listed on the IDX. The time period tested was 5 years, from 2015 to 2019. The population in this study were 26 companies with the sampling technique using purposive sampling method so that the sample taken was 12 companies. Using secondary data obtained from idx.co.id and company data contained on the official website of the respective company. The data analysis technique used is multiple linear regression analysis using SPSS. The results of this study indicate that Sales Growth has a significant negative effect on ROA, while Current Ratio, Debt to Equity Ratio, Total Assets Turnover have no effect on Return on Assets. Based on the results of the Determination Coefficient test which shows that the value of R Square Current Ratio, Debt to Equity Ratio, Total Assets Turnover and Sales Growth to Return on Assets is 0.459 or 45.9%. While the remaining 54.1% is influenced by other variables which were not analyzed in the study.   Penelitian ini bertujuan untuk menganalisis pengaruh Current Ratio, Debt to Equity Ratio, Total Assets Turnover dan Sales Growth Terhadap Return on Asset pada perusahaan manufaktur sub sektor makanan dan minuman yang terdaftar di BEI. Periode jangka waktu yang di ujikan selama 5 tahun yakni dari tahun 2015 sampai 2019. Populasi dalam penelitian ini yaitu sebanyak 26 perusahaan dengan teknik pengambilan sampel menggunakan metode purposive sampling sehingga sampel yang diambil sebanyak 12 perusahaan. Menggunakan data sekunder yang diperoleh dari idx.co.id dan data perusahaan yang terdapat di website resmi perusahaan masing-masing. Teknik analisis data yang digunakan adalah analisis regresi linear berganda dengan menggunakan SPSS . Hasil penelitian ini menunjukkan bahwa Sales Growth berpengaruh negatif signifikan terhadap ROA, sedangkan Current Ratio, Debt to Equity Ratio, Total Assets Turnover tidak berpengaruh terhadap Return on Asset . Berdasarkan hasil uji Koefisien Determinasi yang menunjukkan bahwa nilai R Square Current Ratio, Debt to Equity Ratio, Total Assets Turnover dan Sales Growth terhadap Return on Asset sebesar 0,459 atau 45,9%. Sedangkan sisahnya 54,1% dipengaruhi oleh variabel lain yang tidak dianalisis dalam penelitian tersebut.